Rehabilitation application development using wearable body motion capture sensors - Tan, Yong Seng. (2011)
Nowadays, a lot of researches have been done on rehabilitation of neuron disease patients. Several of motion capture techniques have been applied in the rehabilitation process. This project is mainly focus on development of a wearable rehabilitation device using motion capture sensors. In this project, inertia motion capture system is used and tactors are used as feedback devices to human body. Inertia motion capture system is chosen due to its features of lightweight, high accuracy, small in size, and ability to connect wirelessly with computer interface, these features allow inertia motion capture device wearable on human body.